2001
DOI: 10.1007/s002130000674
|View full text |Cite
|
Sign up to set email alerts
|

Rewarding and locomotor-activating effects of direct dopamine receptor agonists are augmented by chronic food restriction in rats

Abstract: These results indicate that the augmentation of reward by food restriction extends to drugs that bypass the DA terminal and act postsynaptically. When taken together with prior immunohistochemical and behavioral findings, these results suggest that food restriction may increase the "enabling" effect of the D1 receptor on DA-mediated behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 41 publications
1
57
0
1
Order By: Relevance
“…Similarly variable effects have been obtained with D2/3 agonists such as bromocriptine, quinpirole, quinelorane, 7-OH-DPAT [7-hydroxy-2-(di-n-propylamino)tetralin], and U99194A (5,6-dimethoxy-N,N-dipropyl-2,3-dihydro-1H-inden-2-amine) (Nakajima and O'Regan, 1991;Hunt et al, 1994;Ranaldi and Beninger, 1994;Kling-Petersen et al, 1995;Depoortere et al, 1996;Hatcher and Hagan, 1998;Carr et al, 2001Carr et al, , 2002Malanga et al, 2008). For example, quinpirole facilitated ICSS in some studies (Ranaldi and Beninger, 1994;Carr et al, 2001), depressed ICSS in other studies (Rady et al, 1994;Hatcher and Hagan, 1998), and produced variable effects across doses and different ICSS rates in yet other studies (Nakajima and O'Regan, 1991;Depoortere et al, 1996;Malanga et al, 2008). The variable effects of DA agonists on ICSS contrast with the more reliable selfadministration of these compounds in rats and nonhuman primates (Woolverton et al, 1984;Caine and Koob, 1993;Weed et al, 1993;Grech et al, 1996;O'Connor et al, 2011;Huskinson et al, 2014).…”
Section: Icss In Abuse Potential Testingmentioning
confidence: 70%
See 3 more Smart Citations
“…Similarly variable effects have been obtained with D2/3 agonists such as bromocriptine, quinpirole, quinelorane, 7-OH-DPAT [7-hydroxy-2-(di-n-propylamino)tetralin], and U99194A (5,6-dimethoxy-N,N-dipropyl-2,3-dihydro-1H-inden-2-amine) (Nakajima and O'Regan, 1991;Hunt et al, 1994;Ranaldi and Beninger, 1994;Kling-Petersen et al, 1995;Depoortere et al, 1996;Hatcher and Hagan, 1998;Carr et al, 2001Carr et al, , 2002Malanga et al, 2008). For example, quinpirole facilitated ICSS in some studies (Ranaldi and Beninger, 1994;Carr et al, 2001), depressed ICSS in other studies (Rady et al, 1994;Hatcher and Hagan, 1998), and produced variable effects across doses and different ICSS rates in yet other studies (Nakajima and O'Regan, 1991;Depoortere et al, 1996;Malanga et al, 2008). The variable effects of DA agonists on ICSS contrast with the more reliable selfadministration of these compounds in rats and nonhuman primates (Woolverton et al, 1984;Caine and Koob, 1993;Weed et al, 1993;Grech et al, 1996;O'Connor et al, 2011;Huskinson et al, 2014).…”
Section: Icss In Abuse Potential Testingmentioning
confidence: 70%
“…For example, the nonselective D1/D2 agonist apomorphine generally produces only depression of ICSS, although in frequency-rate procedures, high doses of apomorphine may produce weak facilitation of low ICSS rates maintained by low brain stimulation frequencies at doses that also depress high ICSS rates maintained by high frequencies (Liebman and Butcher, 1973;Strecker et al, 1982;Depoortere et al, 1996;Singh et al, 1996). Selective D1 agonists such as SKF38393 [(6)-1-phenyl-2,3,4,5-tetrahydro-(1H)-3-benzazepine-7,8-diol hydrobromide], SKF82958 (3-allyl-6-chloro-1-phenyl-1,2,4,5-tetrahydro-3-benzazepine-7,8-diol), and A77636 [(1R,3S)-3-(1-adamantyl)-1-(aminomethyl)-3,4-dihydro-1H-isochromene-5,6-diol] have been reported to facilitate ICSS in some studies (Nakajima and O'Regan, 1991;Ranaldi and Beninger, 1994;Carr et al, 2001;Gilliss et al, 2002;Malanga et al, 2008), but the magnitude of facilitation is generally weak and may be accompanied by evidence for impaired performance, and other studies have reported only depression by D1 agonists (Hunt et al, 1994;Baldo et al, 1999). Similarly variable effects have been obtained with D2/3 agonists such as bromocriptine, quinpirole, quinelorane, 7-OH-DPAT [7-hydroxy-2-(di-n-propylamino)tetralin], and U99194A (5,6-dimethoxy-N,N-dipropyl-2,3-dihydro-1H-inden-2-amine) (Nakajima and O'Regan, 1991;Hunt et al, 1994;Ranaldi and Beninger, 1994;Kling-Petersen et al, 1995;Depoortere et al, 1996;Hatcher and Hagan, 1998;Carr et al, 2001Carr et al, , 2002Malanga et al, 2008).…”
Section: Icss In Abuse Potential Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…Negative energy balance may thus be critical in establishing food-induced locomotor sensitization. Food restriction both facilitates dopaminergic transmission, especially in the nucleus accumbens (Cadoni et al, 2003;Carr et al, 2003;Haberny et al, 2004;Lindblom et al, 2006), and increases the rewarding and stimulant properties of dopamine receptor agonists (Carr et al, 2001) and stimulant drugs (Deroche et al, 1993;Bell et al, 1997;Cabeza de Vaca et al, 2004). Facilitation of dopaminergic transmission in nucleus accumbens, and plasticity in associated pathways (Haberny et al, 2004;Haberny and Carr, 2005) may be a prerequisite for establishing behavioral sensitization to food.…”
Section: Discussionmentioning
confidence: 99%